Examining English Proficiency Variations between Male and Female Students in Thailand - Matthew Rudd (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2018)
The central objective of this study was to investigate the influence of gender on English language proficiency scores among Thai students in Bangkok. To bring this research ambition to fruition, a mixed methods research design was utilised to collate qualitative and quantitative data. The former was gathered from interviews with 20 well-established educatorsto canvass their perceptions regardingthe potential role of gender in students’English language proficiency levels. The quantitative data involved t-test analyses (0.05) of students’ formal English examination results from three separate sample clusters (N = 863), which included: (1) senior high school students (n = 72); (2) third year private university students (n = 684); and, (3) first year students at a government university (n = 107). The findings disclosed that (1) English teachers distinguished girls as ostensibly more attentive and more highly motivated; (2) female students’ English proficiency scores were significantly higher than their male counterparts across both university clusters, and, marginally higher at the high school level; and therefore,(3) the students’ formal examination results added firm support the educators’ perception that female students demonstrate greater proficiency in English due to exhibiting higher degrees of motivation and focus